Eksplorasi Strategi Pembelajaran Inovatif Berbasis Teknologi Guru Milenial. - Said, Rahmat (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
ABSTRACT This study aims to explore innovative technology-based learning strategies implemented by millennial teachers at SDN 182 Angin-Angin, Enrekang Regency, South Sulawesi. The research addresses issues related to the forms of technology-based learning strategies used, supporting and inhibiting factors in their implementation, and their impact on student engagement and motivation. A qualitative approach with a descriptive-exploratory method was employed, utilizing in-depth interviews, classroom observations, and documentation for data collection. The results indicate that millennial teachers actively utilize interactive digital media, educational applications, and gamification methods to enhance student participation and motivation. The availability of internet access and teachers’ openness to innovation are key supporting factors, while limited infrastructure and technology training are major obstacles. The implementation of these strategies has a positive impact on increasing student engagement, developing critical thinking skills, and boosting learning motivation. The study recommends ongoing support from schools and the government in providing infrastructure and teacher training to optimize technology integration in learning. Keywords: innovative learning strategies, millennial teachers, educational technology